A Photohadronic Interpretation of H.E.S.S. Afterglow Observations of GRB 221009A - Sarira Sahu; B. Medina-Carrillo; D. I. Páez-Sánchez; G. Sánchez-Colón; Subhash Rajpoot (The Astrophysical Journal, 2024)
The High Energy Stereoscopic System (H.E.S.S.) started observing the extremely powerful long-duration gamma-ray burst (GRB) GRB 221009A starting 53 hr after the triggering event. The H.E.S.S. collaboration carried out observations on 2022 October 11, 12, and 17 under poor atmospheric conditions, without detecting significant very-high-energy photons from the source and computed the upper limits of the fluxes for the different nights. We study these flux upper limits by using the photohadronic model and show that the interaction of high-energy protons with synchrotron seed photons in the forward-shock region of the GRB jet exhibits behavior compatible with the upper limits computed by the H.E.S.S. collaboration.